Pengaruh Biochar Berbasis Biofertilizer untuk Meningkatkan Produksi Sawi (Brassica juncea L.) - Suseno Ari Wibowo; Eko Chandra Wiguna; Buana Susilo; Lengga Nurullah Dalimartha; Endry Nugroho Prasetiyo (Universitas Sebelas Maret, 2017)
Mustard high-yield plantation are mostly supported by utilization of inorganic fertilizer. However, this couldincrease soil acidity and give negative impact to the environment. Biochar, a soil amendment, has potential asa valuable tool for the agricultural with ability to help build soil, conserve water, and sequester carbon. Further,biochar could be as well combined with biofertilizer to increase soil nutrient. This study aims to understand theinfluence of combining biochar with biofertilizer on mustard yield plantation..Ten groups of combination wascarried out on this study namely P1: without fertilizer (control), P2:biochar, P3:NPK, P4:biochar + bacteria,P5:biochar + mycorrhizal, P6:biochar + NPK, P7:biochar + bacteria + NPK, P8:biochar + mycorrhizal + NPK,P9:biochar + mycorrhizal + bacteria, P10:biochar + bacteria + mycorrhizal + NPK. The addition of biochar onbiofertilizer showed significantly increasing of mustard biomass and yield by 6,85 gram and 12015 kg/harecpectively.